Sex Crimes Against Children in Indonesia And the Prevention Model - Rosyadi, Khoirul (Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Sex crimes against children in Indonesia have repeatedly continued to occur. Moreover, it has experienced an increase in both quantity and quality. To prevent this, a model for the prevention of sex crimes against children in Indonesia is required. The purpose of this study was to look for a model of prevention of sex crimes against children in Indonesia through sex education (reproductive health). The study used qualitative research with a phenomenological approach. The study was conducted in 6 (six) provinces in Indonesia, namely East Java, West Java, Jakarta, Ambon, Aceh, and West Kalimantan. The results obtained from this study showed that sex crimes against children in Indonesia occur due to various factors, namely: lack of knowledge about sexuality, the lack of faith, technological development, economic, internet, pornography, individualist and permissive culture, and the family issues of the perpetrators. The result of this study found a model for the prevention of sex crimes against children in Indonesia based on sex education (reproductive health). Nevertheless, this study recommends that the implementation of a model of prevention of sex crimes against children in Indonesia through sex education (reproductive health) will work if there is a synergy between stakeholders, the state (government), schools, and the community.